Effects of Phosphate Binders in Moderate CKD - Block, Geoffrey A.; Wheeler, David C.; Persky, Martha S.; Kestenbaum, Bryan; Ketteler, Markus; Spiegel, David M.; Allison, Matthew A.; Asplin, John; Smits, Gerard; Hoofnagle, Andrew N.; Kooienga, Laura; Thadhani, Ravi; et al. (Journal of the American Society of Nephrology, 2012)
Some propose using phosphate binders in the CKD population given the association between higher levels of phosphorus and mortality, but their safety and efficacy in this population are not well understood. Here, we aimed to determine the effects of phosphate binders on parameters of mineral metabolism and vascular calcification among patients with moderate to advanced CKD. We randomly assigned 148 patients with estimated GFR=20-45 ml/min per 1.73 m(2) to calcium acetate, lanthanum carbonate, sevelamer carbonate, or placebo. The primary endpoint was change in mean serum phosphorus from baseline to the average of months 3, 6, and 9. Serum phosphorus decreased from a baseline mean of 4.2 mg/dl in both active and placebo arms to 3.9 mg/dl with active therapy and 4.1 mg/dl with placebo (P=0.03). Phosphate binders, but not placebo, decreased mean 24-hour urine phosphorus by 22%. Median serum intact parathyroid hormone remained stable with active therapy and increased with placebo (P=0.002). Active therapy did not significantly affect plasma C-terminal fibroblast growth factor 23 levels. Active therapy did, however, significantly increase calcification of the coronary arteries and abdominal aorta (coronary: median increases of 18.1% versus 0.6%, P=0.05; abdominal aorta: median increases of 15.4% versus 3.4%, P=0.03). In conclusion, phosphate binders significantly lower serum and urinary phosphorus and attenuate progression of secondary hyperparathyroidism among patients with CKD who have normal or near-normal levels of serum phosphorus; however, they also promote the progression of vascular calcification. The safety and efficacy of phosphate binders in CKD remain uncertain.